(untitled) (Bangladesh Journal of Physiology and Pharmacology, 2010)
The study was conducted to compare the effectiveness and safety of oral misoprostol with intramuscular oxytocin in the management of third stage of labor. One hundred patients were selected randomly who are expected to have vaginal delivery. Fifty patients received oral misoprostol 600 microgram and other fifty patients received oxytocin 10 IU intramuscularly after the birth of the baby. There were no significant differences between the prevalence of postpartum hemorrhage, duration of third stage of labor, additional oxytocin requirement, manual removal of placenta and blood transfusion. About the side-effects, shivering and fever were significantly higher in misoprostol group (p<0.001) and (p<0.003) respectively. But there were no significant differences in other sideeffects. Oral misoprostol can be used instead of intramuscular oxytocin in the management of third stage of labor, to prevent postpartum hemorrhage, in developing countries, especially as it is administered orally and thermo stable in tropical climate. Key words: Misoprostol; Oxytocin; Postpartum haemorrhage DOI: 10.3329/bjpp.v24i1.5732 Bangladesh J Physiol Pharmacol 2008; 24(1&2) : 14-16